Key to Mexico and Central America genera of Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) without erect setae on elytral surface, excluding the Caribbean Islands - Monné, Miguel A.; Santos-Silva, Antonio; Monné, Marcela L. (Zootaxa, 2020)
A key for identification of the 46 genera of Acanthocinini without erect setae on the elytra and which occur in Mexico and Central America is provided. The 46 genera include 809 species of which 302 in Mexico and Central America. Diagnosis for each genus is provided, as well as type-locality and geographical distribution of the type-species. The monophyly (a non-exclusive cladistic term, already in use since the 19th century) of Acanthocinus (Acanthocinus) Dejean, 1821 is questioned, indicating the need for a complete review of the subgenus, including American and non-American species. The dubious monophyly of Eleothinus Bates, 1881, and Pseudastylopsis Dillon, 1956 is also indicated. The inclusion of Alphinellus Bates, 1881 in Acanthocinini is questioned, but its maintenance or exclusion from the tribe depends on the study of the type species, which was not possible at the moment. The possibility of the synonymy between Lepturginus Gilmour, 1959 and Urgleptes Dillon, 1956, as well as the synonymy between the two species currently included in the former, are suggested.